The Role of the Flagellar Protein FlgJ in the Virulence of Brucella abortus - Coloma-Rivero, Roberto F.; Gómez, Leonardo; Alvarez, Francisco; Saitz, Waleska; del Canto, Felipe; Céspedes, Sandra; Vidal, Roberto; Oñate, Angel A. (Frontiers in Cellular and Infection Microbiology, 2020)
Brucella abortus is a facultative intracellular pathogen that causes a zoonosis called brucellosis. This disease leads to abortion and infertility in cattle, and diverse complications in humans. B. abortus is a successful intracellular bacterium that has developed the ability to evade the host’s immune system and it replicates in professional and non-professional phagocytic cells, persisting in the different tissues and organs of its hosts. It has been described that Brucella expresses a polar flagellum under certain conditions, but its function is still unknown. In this study we evaluated the role of the FlgJ, a protein, presumably a peptidoglycan hydrolase involved in flagellum formation and in the virulence of B. abortus strain 2308. B. abortus 2308 ΔflgJ mutant and complemented strains were constructed to study the function of the FlgJ protein in the context of the virulence of this pathogen in in vitro and in vivo assays. The results showed that the elimination of the flgJ gene delays the growth rate of B. abortus in culture, reduces its intracellular survival capacity in professional and non-professional phagocytic cells, rendering it unable to escape from the endocytic route and not reaching the endoplasmic reticulum. It also negatively affects their persistence in BALB/c mice. Functionally, the B. abortus 2308 flgJ gene restored motility to an E. coli flgJ mutant gene. Furthermore, it was discovered that the production of FlgJ protein is associated with the bacterial adherence by B. abortus. Therefore, although the specific function of the polar flagellum for Brucella is unknown, the data indicates that the flagellar flgJ gene and its product are required for full virulence of B. abortus 2308, since its deletion significantly reduces the fitness of this pathogen in vitro and in vivo.